Membangun Desa Cerdas: Peran Abdi Masyarakat dalam Transformasi Digital Pelayanan Publik - Nurdin Nurdin (Jurnal Pengabdian Masyarakat, 2026)
Digital transformation in rural areas has become a strategic agenda to strengthen public service governance that is efficient, inclusive, and adaptive. This study aims to analyze the role of Community Service Actors, the key factors affecting smart village implementation, the common challenges leading to ceremonial and unsustainable digital village programs, and to propose a sustainable community mentoring model to support digital transformation and empower rural MSMEs. This research adopts a literature review method focusing on publications from 2020-2025. Findings indicate that Community Service Actors function as catalysts through knowledge transfer, digital literacy enhancement, and both technical and socio-institutional support. The effectiveness of smart village implementation is determined by three interrelated pillars: digital literacy, smart governance, and community participation. However, many initiatives face obstacles such as infrastructure-focused programs without human capacity strengthening, low digital competence among village apparatus, weak multi-stakeholder collaboration, and socio-cultural resistance. To address these issues, this study proposes a sustainable mentoring model based on needs assessment, participatory program design, a training–mentoring–monitoring scheme, development of local champions, integration of digital governance, and program ownership transfer. This model is expected to foster long-term digital transformation and strengthen technology-based MSME empowerment in rural communities.